Prioritizing Health Information in Europe – What do we want and need to know?. (13th November 2019) - Fehr, A; Ombrellaro, K J; Achterberg, P; Bogaert, P; Carle, F; Palmieri, L; Tijhuis, M J; Lyons, R; Zelviene, A; Ziese, T
Abstract: Background: Prioritization of Health information (HI) involves the establishment of methodological standards, and the development of political momentum to reliably track health status and health determinants. This is important in order to strengthen the evidence base for public health policies and facilitate effective delivery of healthcare services. In support of the establishment of a sustainable EU-wide Health information system, this consortium explores how HI is prioritized in EU and associated countries. Methods: The Robert Koch Institute is conducting an online Policy Delphi survey among InfAct project partners, stakeholders from EU-Member States and associated countries. The Delphi methodology allows for rankings and priority-setting among a group of experts. The Policy Delphi facilitates the analysis of the impact and acceptability of a proposed policy option. The survey targets experts in national public health institutes and agencies, ministries of health and research. Participants are invited to provide information regarding their national HI prioritization processes, and to rank prioritization strategies and criteria, according to their degree of "desirability", "feasibility", "importance" and "confidence". Results: The Delphi survey will compile and assess processes and methods used to prioritize health information at national level in the EU and associated countries. The expected outcome is a list of good-practices in health information development and prioritization within countries, which could be further integrated to a health information prioritization strategy at the European level. Conclusions: Prioritizing health information ensures that the right data is collected, is used to support ongoing public health policy action, and to capture emerging public health issues. This overview of prioritization strategies and methods aims to promote evidence-based public health by structuring exchanges about national HI prioritization in Europe.